sites.google.com/view/Lapinskas – Mathematical readings - Lapinskas, Remigijus (Lietuvos matematikos rinkinys, 2023)
This article is about the author's online book "Mathematical Readings" [2]. The book presents the high school math course in a slightly different way than conventional textbooks, the work focuses less on routine problems and tries to examine mathematical concepts in a broader context. The book makes frequent use of mobile math apps and the R program, and links to online sources are often provided. The text may be useful for self-study and math circles.
Keywords: math in high school; math circle